Investigating the microbiota of fermented fish products (Pla-ra) from different communities of northeastern Thailand. - Rutchanee Rodpai; Oranuch Sanpool; Tongjit Thanchomnang; Arporn Wangwiwatsin; Lakkhana Sadaow; Weeraya Phupiewkham; Patcharaporn Boonroumkaew; Pewpan M Intapan; Wanchai Maleewong (PLoS ONE)
DNA-sequencing was performed on the V3-V4 regions of 16S rRNA genes to investigate the microbial diversity of five samples of fermented freshwater fish (pla-ra) from three provinces in northeastern Thailand. The samples had salt concentrations ranging from 7 to 10%, pH values from 4.83 to 7.15, and D-/L-lactic acid concentrations of 90 to 450 mg/l. A total of 598 operational taxonomic units were annotated at various taxonomic ranks based on the SILVA Database. The lactic-acid and halophilic genera Tetragenococcus, Halanaerobium and Lactobacillus were among the dominant taxa of bacteria. The top 20 non-redundant taxa were considered in more detail. In two pla-ra samples, Tetragenococcus muriaticus was commonly identified. Halanaerobium fermentans was the most abundant species in a third sample and co-dominant in another sample. Lactobacillus rennini was dominant in the pla-ra sample from Roi Et Province. Additionally, other beneficial bacteria were detected including Staphylococcus nepalensis, Lactobacillus sakei, Lactobacillus pentosus, Weissella confusa, and Bifidobacterium bifidum. Differences between samples may be due to use of different raw materials, salt concentrations, recipes, processes and fermentation periods. The microbial communities in pla-ra provide a better understanding of the production outcomes of traditional products. Further optimization of the fermentation process, for example by using dominant bacterial taxa in starter cultures, may improve processes of food fermentation, food quality and flavor control, providing useful guidelines for industrial applications.